Evaluation of the Financial Performance Efficiency of Rashid Bank in Wasit Governorate/Al-Numaniyah Branch for the Period 2015–2023 - Doaa Bassem Obeid; Ruwa Nasir Kazi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The study aims to explain the concept of evaluating the efficiency of financial and economic performance in government commercial banks, specifically focusing on Rasheed Bank’s Al-Numaniyah Branch, for the period 2015-2023. The study highlights the importance of using specific criteria or indicators to assess the financial and economic performance of the bank, particularly its efficiency in managing assets and liabilities. The research identifies key financial ratios such as the trading ratio, which increased to 2:1 in 2023 compared to 1:2 in 2020. This increase indicates that the current assets are now twice the value of current liabilities, offering security to the bank’s stakeholders and creditors. This improved ratio is a significant sign of financial stability and effective asset management, offering valuable insights into the bank's financial health. The research also emphasizes the necessity of evaluating the management of current assets and liabilities. It recommends that the bank focus on optimizing the use of its current assets while harmonizing the sources of its funds to maximize profitability. Additionally, it is crucial to manage the liquidity ratio effectively, balancing the need for financial security with the risks involved in liquidity management. This study suggests that the bank should implement strategies to enhance the profitability of its assets, ensuring that investment decisions align with long-term economic and financial goals. In conclusion, the study underscores the importance of strategic financial management, including a comprehensive evaluation of both financial and economic performance, to ensure the bank's sustainability, profitability, and growth in the ever-evolving banking landscape, fostering long-term financial stability and success.